(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
The Modified Foamed Concrete (FC) was acheived by replacing sand with Rice Husk Ash (RHA) and experimental result has shown an increased in the compressive strength compared to conventional FC. This increase in compressive strength is required by FC to withstand impact loading. The experimental parameters from the modified FC subjected to impact loading were incorporated into previous empirical formula's, such as National Defense Research Committee (NDRC) [8], [18]), Ammann & Whitney [8], and Hughes [9] formulas. The calculation showed differences in results due to its variation and multiple approaches of the empirical formula. However, it is noted that the modified FC did not produce much differences with the conventional FC when it is subjected to impact loading. The calculation of previous formulas have indicated and highlighted these findings.Â Â Â